(untitled) (Fiep Bulletin - online, 2024)
Introduction: 20 years ago, the Education Guidelines and Bases Law was amended, through Law 10.639/03, establishing the mandatory teaching of African and Afro-Brazilian History and Culture in basic education. Objective: In this way, this work sought to analyze the perception of academics from the Degree in Physical Education course at UNIG/Itaperuna regarding the use of Traditional African Games as a way of approaching Law 10.639/03. Methods: For this, the Survey method was applied as a strategy for analyzing the population’s opinions based on the responses obtained through a questionnaire. Results: Based on reading the data collected, it was noted that only 56% of participants already knew the law, and all participants responded that it is possible to address content relating to Afro-Brazilian History and Culture in Physical Education through traditional games Africans. Conclusion: Therefore, it is concluded that it is necessary for higher education institutions to provide future teachers with knowledge about Law 10.639/03 as well as ways of approaching Traditional African Games within the discipline of Physical Education.